2010
DOI: 10.1007/s11199-010-9746-x
|View full text |Cite
|
Sign up to set email alerts
|

There’s More Than Meets the Eye: Facial Appearance and Evaluations of Transsexual People

Abstract: Recent events have drawn attention to the prejudice and discrimination faced by transpeople; however, there is limited research on attitudes toward transpeople. We studied the effects of facial appearance on the evaluations of transsexuals in 239 heterosexual undergraduate students from the midwestern United States. Men had significantly more negative evaluations than women. The gender of the transsexual (male-to-female or female-to-male) had limited effects on evaluations; however, the transsexual whose facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
78
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 64 publications
8
78
1
1
Order By: Relevance
“…Moreover, based on the analysis of three pairs of items that compared people's attitudes toward transwomen with attitudes toward transmen, Winter et al (2008) found that women and men reported more negative attitudes toward transwomen than transmen. In contrast, Gerhardstein and Anderson (2010) found a similar result but only for men. King et al (2009) King et al (2009) found that the term Hong Kong people most commonly use to describe transpeople is "yen yiu," which means "human monster."…”
Section: Gender Differences In Attitudes Toward Transpeoplementioning
confidence: 66%
See 4 more Smart Citations
“…Moreover, based on the analysis of three pairs of items that compared people's attitudes toward transwomen with attitudes toward transmen, Winter et al (2008) found that women and men reported more negative attitudes toward transwomen than transmen. In contrast, Gerhardstein and Anderson (2010) found a similar result but only for men. King et al (2009) King et al (2009) found that the term Hong Kong people most commonly use to describe transpeople is "yen yiu," which means "human monster."…”
Section: Gender Differences In Attitudes Toward Transpeoplementioning
confidence: 66%
“…Participants rated vignettes with images of hypothetical transsexual individuals and completed questionnaires measuring transprejudice, sexual prejudice, and social desirability. Gerhardstein and Anderson (2010) found that men reported more negative general evaluations of the transsexual character than women, but the general evaluations of men and women did not discriminate significantly between transwomen and transmen characters. They also found that men reported more transprejudice than women and more violence, teasing, and discomfort towards transwomen than transmen, whereas women did not discriminate between transwomen and transmen for the violence, teasing, and discomfort ratings.…”
Section: Gender Differences In Attitudes Toward Transpeoplementioning
confidence: 79%
See 3 more Smart Citations